A Prediction Model of the Incidence of Nonalcoholic Fatty Liver Disease With Visceral Fatty Obesity: A General Population-Based Study - Zhou, Yang; Chai, Xiangping; Guo, Tuo; Pu, Yuting; Zeng, Mengping; Zhong, Aifang; Yang, Guifang; Cai, Jiajia (Frontiers in Public Health, 2022)
Objective: This study aimed to distinguish the risk variables of nonalcoholic fatty liver disease (NAFLD) and to construct a prediction model of NAFLD in visceral fat obesity in Japanese adults. Methods: This study is a historical cohort study included 1516 individuals with visceral obesity. All individuals were randomly divided into training group and validation group at 70% (n = 1061) and 30% (n = 455), respectively. The LASSO method and multivariate regression analysis were performed for selecting risk factors in training group. Then, overlapping features were selected to screen the effective and suitable risk variables for NAFLD with visceral fatty obesity, and a nomogram incorporating the selected risk factors in the training group was construct. Then, we used the C-index, calibration plot, decision curve analysis, and cumulative hazard analysis to test the discrimination, calibration, and clinical meaning of the nomogram. At last, internal validation were used in validation group. Results: We contract a nomogram and validated it using easily and cost-effective available parameters to predict incidence of NAFLD in participants with visceral fatty obesity, including ALT, HbA1c, body weight, FPG, and TG. In training cohort, the area under the ROC was 0.863, 95%CI was 0.84-0.885. In validation cohort, C-index was 0.887, 95%CI was 0.857-0.888. The decision curve analysis showed the model’s prediction is more effective. Decision curve analysis of the training cohort and validation cohort showed that the predictive model was more effective in predicting the risk of NAFLD in Japanese patients with visceral fatty obesity. To help researchers and clinicians better use the nomogram, our online version can be accessed at https://xy2yyjzyxk.shinyapps.io/NAFLD/. Conclusions: Most patients with visceral fatty obesity have a risk with NALFD, but some will not develop into it. The presented nomogram can accurately identify these patients at high risk.